La justicia administrativa en España - Meilán Gil, José Luis (Revista de Derecho, 2019)
The present work contains an analysis of the contentious-administrative Jurisdiction in Spain, taking as starting point the profound revision produced in the judicial system by the approval of the 1978 Spanish Constitution. Some of the most significant aspects of the current regulation, contained in Law 29/1998, dated July 13th are taken into account.